Sick of waiting: Does waiting for elective treatment cause sickness absence?. Issue 12 (December 2016) - Dyrstad, Karin; Halvorsen, Thomas; Hem, Karl-Gerhard; Rohde, Tarald
Highlights: We use Norwegian register data on sickness absence and waiting time and treatment in specialist health care. We model the effect of waiting times in specialist health care among Norwegian employees. Waiting times for specialist health care does not have a substantial effect on the duration of sickness absence. Reducing waiting times in specialist health care will probably not affect overall sickness absence. Abstract: Sickness absence represents a substantial cost in most of Western Europe, whether the insurance scheme is public or private. The objective of this study was to analyse whether waiting time for elective treatment in specialist health care is associated with the length of individual sickness absence in Norway. To estimate the association between waiting time and the duration of sick leave, we used data from the working population aged 18–67 years in 2010–2012. The files combined register data from The Norwegian Patient Registry with individual characteristics and sickness absence data from Statistics Norway, and was analysed using zero-truncated negative binomial regression. We found that about one in four employees who had one or more spells of sick leave in the period, was also waiting for consultation or treatment in specialist health care. Yet, the length of the waiting period had no substantial effect on the length of sickness absence (i.e., less than 0.1% reduction). Therefore, while measures to reduce waiting times for hospital treatment in many instances could be beneficial for the individual patient, such policies would probably not have any substantial impact on the national sickness absence rate.